Stock Market Betas for Cyclical and Defensive Sectors: A Practitioner’s Perspective - Asinas, Mark Adrian S. (Philippine Management Review, 2019)
Companies can be categorized as cyclical or defensive based on their performance in various phases of the business cycle.  Cyclical companies exhibit performance directly related to the business cycle, while defensive companies tend to display stability in the face of economic booms and busts.  Given the link between earnings and stock price, as well as the stock market index as an indicator of the economic cycle, cyclical company stocks are commonly expected to exhibit returns highly correlated to the stock market index, while returns on defensive company stocks are generally believed to display low correlation to index returns.  The above is especially useful in equity valuation, particularly in the use of the capital asset pricing model (CAPM) and the beta coefficient, where analysts typically perform valuation sense-checks on the beta variable – cyclical company stocks should generally have beta coefficients greater than 1, while defensive company stocks should generally have beta coefficients less than 1.  Based on selected Philippine stock price data, the above sense-check holds true for defensive company stocks, while it does not hold true for cyclical company stocks.